Membracidos de colombia - i. revisión parcial de las especies del género alchisme kirkaldy (homoptera: membracidae: hoplophorioninae) (1980)
The genus Alchisme Kirkaldy was revised. From nineteen species listed by Metcalf (1965) not specimens were obtained of eight of them. Original descriptions of these species are included and tentatively are localized in the key.  A redescription is given for the species A. bos (Fairmaire), A. fastidiosa (Fairmaire), A. grossa (Fairmaire), A. inermis (Fairmaire), A. nigrocarinata (Fairmaire), A. rubrocostata (Spinola), A. turrita (Germar), A. ustulata (Fairmaire), A. virescens (Fairmaire) y A. nigrocarinata var. tridentata (Fairmaire), for which was used the original combination A. tridentata (Fairmaire). A. projecta Funkhouser was synonymized in A. bos (Fairmaire). The main pronotum characters and male genitalia are illustred; Scanning Electro Microscope pictures of the aedeagus of the insects were observed and obtained and are included as part of the illustrations. Geographic distributionsof the genus was analized and maps were prepared.